1995
DOI: 10.1099/0022-1317-76-9-2131
|View full text |Cite
|
Sign up to set email alerts
|

Properties of modified hepatitis B virus surface antigen particles carrying preS epitopes

Abstract: The current hepatitis B virus (HBV) vaccines contain the small (S) and middle (M) viral envelope proteins in particulate form but lack the large (L) protein. Although these particles elicit protective immunity to HBV, inclusion of the immunogenic preS1 region of the L protein may enhance their efficacy. To present preS1-derived epitopes on secretable subviral particles we rearranged the HBV envelope ORF by fusing part or all of the preS 1 region to either the N or C terminus of the S protein. Fusion of the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Our data suggest that the "a" determinants on the WHsAg are quite different. Our data confirm the importance of anti-pre-S2 Abs, which has been suggested before (15,16,28). This supports the notion that a new generation of anti-HBV vaccine should contain this epitope.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data suggest that the "a" determinants on the WHsAg are quite different. Our data confirm the importance of anti-pre-S2 Abs, which has been suggested before (15,16,28). This supports the notion that a new generation of anti-HBV vaccine should contain this epitope.…”
Section: Discussionsupporting
confidence: 92%
“…1A). Most human and murine anti-S Abs bind to the conformational "a" determinant located at the S 120 -147 region (1,(15)(16)(17). In H-2 d and H-2 b mice, Ab responses but not CTL responses are readily primed against determinants in the pre-S2 domain of HBsAg (11).…”
Section: Construction Of Chimeric Ms Ags Of Hbv and Whvmentioning
confidence: 99%
“…A natural HBV point mutant unable to express the M protein was isolated from a patient and demonstrated that this protein is not required [125] , whereas suppression of L or S expression impeded virion formation [122,123] . An L construct with an N-terminally fused secretion signal g enerating only the e-preS conformation was secreted as a component of subviral particles [126] but failed to support virion formation [58] . Apparently, the i-preS conformation of L exposing the preS domain at the cytosolic side of the ER was essential for nucleocapsid envelopment.…”
Section: Formationmentioning
confidence: 99%
“…The intracellular LS protein with additional preS1 and preS2 domains N-terminal to the S region is expressed as nonglycosylated p39 and glycosylated gp42 (3). All three HBsAg species form particulate structures when expressed individually (2)(3)(4). The MS and S Ags are efficiently secreted from transfected cells, whereas the LS Ag is exclusively found intracellularly (3).…”
mentioning
confidence: 99%
“…Hepatitis B surface Ag (HBsAg) 4 secreted by HBV-infected hepatocytes and present in the plasma of infected individuals is a complex macromolecule composed of proteins and lipids (1,2). The 22-nm coreless HBsAg lipoprotein particles contain three natural variants of HBsAg designated large (LS), middle (MS), and small (S) surface proteins.…”
mentioning
confidence: 99%